APPLICATION IRON AND ALUMINUM ELECTRODES IN EMISSION SPECTROGRAPH FOR ANALYZING BORON AND CADMIUM IN URANIUM NUCLEAR FUEL - Sahat Simbolon (PTBN - BATAN, 2008)
ABSTRACT APPLICATION OF IRON AND ALUMINUM ELECTRODES IN SPECTROGRAPH EMISSION FOR ANALYZING BORON AND CADMIUM IN URANIUM NUCLEAR FUEL. Analysis of boron and cadmium in nuclear fuel was carried out using iron and aluminum electrodes as well as X-ray film photographic for thorax in emission spectrograph. DC arc excitation source could not be used for iron and aluminum electrodes, since both electrodes melt even at current less than 10 ampere and excitation time less than 2 seconds. AC sparks excitation source using iron and aluminum electrodes could be used for analyzing boron and cadmium after extraction of uranium in nuclear fuel using TBP-kerosene solution. Graphite electrode was also utilized to analyze boron and cadmium with ac sparks method for comparison. X-ray film photographic for thorax was used to replace glass photographic film SA-1. Halogens elements could not be analyzed using this method because they needed higher temperature for excitation. Calibration curves for boron and cadmium were prepared for each electrode for quantitative analysis, sensitivity calculation and detection limit. It was found that the sensitivity for cadmium metal using aluminum electrode was higher than that using iron electrode, even with respect to graphite electrode. Limit of detection of cadmium using aluminum electrode was the lowest although its intercept was the highest. On the other hand, limit of detection of boron using graphite electrode was the lowest but its intercept was the highest. FREE TERMS: Iron and aluminum electrodes, Emission spectrograph, Graphite electrode ABSTRAK PENGGUNAAN ELEKTRODE BESI DAN ALUMINIUM PADA SPEKTROGRAFI EMISI UNTUK ANALISIS BORON DAN KADMIUM DALAM BAHAN BAKAR NUKLIR URANIUM. Analisis boron dan kadmium dalam bahan bakar nuklir dilakukan menggunakan elektrode besi dan aluminium serta pelat film sinar-X untuk toraks pada spektrografi emisi. Sumber eksitasi dc arc tidak dapat digunakan untuk elektrode besi dan aluminium karena kedua elektrode tersebut meleleh meskipun arus kurang dari 10 A dan waktu eksitasi kurang dari 2 detik. Sumber eksitasi ac sparks menggunakan elektrode besi dan aluminium dapat digunakan untuk analisis boron dan kadmium setelah uranium dalam bahan bakar nuklir diekstraksi menggunakan larutan TBP-kerosin. Elektrode grafit juga digunakan untuk analisis boron dan kadmium dengan menggunakan sumber eksitasi ac sparks sebagai perbandingan. Pelat film sinar-X untuk toraks digunakan untuk menggantikan film gelas fotografi SA-1. Unsur-unsur halogen tidak dapat dianalisis dengan metode ini karena unsur-unsur halogen membutuhkan suhu yang lebih tinggi untuk eksitasi. Kurva kalibrasi untuk boron dan kadmium dibuat untuk setiap elektrode untuk analisis kuantitatif, perhitungan sensitivitas dan batas deteksi. Hasil menunjukkan sensitivitas untuk logam kadmium menggunakan elektrode aluminium lebih tinggi dibandingkan elektrode besi, bahkan terhadap elektrode grafit. Batas deteksi kadmium menggunakan elektrode aluminium paling rendah tetapi nilai titik potongnya paling tinggi. Sebaliknya, batas deteksi boron menggunakan elektrode grafit paling rendah tetapi nilai titik potongnya paling tinggi.KATA KUNCI: Elektrode besi, Elektrode aluminium, Spektrografi emisi, Elektrode grafit